Data cities and astrospatial architecture: An urban ethos from electromagnetic fluxes. Issue 1 (June 2020) - Jackson, D
Abstract: Light remains the origin and sustenance of all forms of life on Earth—but human living is being transformed by ingenious applications of astrospatial technologies that were devised to fly to other planets. This century's networked architectures of semiconductors, satellites, scanners and sensors manipulate diverse electromagnetic frequencies to convert light into unprecedented formats and contents of data that are destined to inform most human behaviours in future. Telematics and informatics are taking our civilisation far beyond the milieu of modernism enabled by Edison's 1879 demonstration of electric incandescence, and the transmillennial 'digital age' underpinned by portable computers and mobile telephony.